Emotional intelligence and organizational commitment: An affective association in the context of Lebanese universities - Younis, Joumana A; Ramahy, Ali Al; Massoud, Mazen; Alemanno, Sylvie (International Journal of Innovative Research and Scientific Studies, 2024)
This paper aims to assess the influence of emotional intelligence on organizational commitment. A quantitative survey was conducted among the academic staff of Lebanese universities to reach this objective. This research paper is an explanatory, descriptive, and confirmatory study. This cross-sectional study is based on a quantitative method to examine the validity of the theory or model. This research favors the deductive approach. This approach enables the deduction of a general conclusion from hypotheses. The structured questionnaire is constructed on the theoretical constructs of the mixed approach of the Goleman model, evaluating the following six components: self-awareness, self-control, internal motivation, empathy, leadership skills, and interpersonal relationship management. Empirical testing incorporates the plurality of causes and effects of interaction in this explanatory, descriptive research. Universities confront a lack of employee commitment. Emotional appreciation drives commitment to the organization. E.I. denotes the aptitude to detect, categorize, and use feelings to smooth rational decisions. The study verified that E.I. components significantly and positively influence organizational commitment, with internal motivation having the highest influence in Lebanese universities. Soft skills are essential abilities. Decision-makers and managers of Lebanese universities, conscious and attentive to the influence of employees' emotions, should integrate emotional intelligence into their managerial practices. To build and maintain organizational commitment, displaying appropriate emotions, interpersonal relationships, and communication are compulsory.